2017
DOI: 10.1021/jacs.7b04499
|View full text |Cite
|
Sign up to set email alerts
|

Radical Cage Effects: The Prediction of Radical Cage Pair Recombination Efficiencies Using Microviscosity Across a Range of Solvent Types

Abstract: This study reports a method for correlating the radical recombination efficiencies (F cP ) of geminate radical cage pairs to the properties of the solvent. Although bulk viscosity (macroviscosity) is typically used to predict or interpret radical recombination efficiencies, the work reported here shows that microviscosity is a much better parameter. The use of microviscosity is valid over a range of different solvent system types, including nonpolar, aromatic, polar, and hydrogen bonding solvents. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 74 publications
4
51
0
Order By: Relevance
“…In two studies by Tyler, the cage effect was found to be highly correlated to solvent microviscosities (measured by DOSY NMR of a probe molecule) and not bulk viscosities, in mixtures of both protic and aprotic solvents. 87,88 Applying an understanding and quantication of microviscosities to MHAT cage effects may enable synthetic chemists to tune the "strength" of the solvent cage through careful selection of solvent and/or solvent mixtures.…”
Section: Understanding Factors That Govern Cage Effectsmentioning
confidence: 99%
“…In two studies by Tyler, the cage effect was found to be highly correlated to solvent microviscosities (measured by DOSY NMR of a probe molecule) and not bulk viscosities, in mixtures of both protic and aprotic solvents. 87,88 Applying an understanding and quantication of microviscosities to MHAT cage effects may enable synthetic chemists to tune the "strength" of the solvent cage through careful selection of solvent and/or solvent mixtures.…”
Section: Understanding Factors That Govern Cage Effectsmentioning
confidence: 99%
“…Recently,T yler demonstratedt hat microviscosity,w hichi si nversely proportional to the translational diffusion coefficient of ap article in Brownian motion,i sab etter parameter than bulk viscosity for correlation with the recombination efficiency of a radicalp air in as olventc age, [20,21] because the solventc age effect is al ocalized phenomenon. Although Cp'Mo(CO 3 )( Cp' = h 5 -CH 3 C 5 H 4 )r adicalg enerated from [Cp'Mo(CO 3 )] 2 by direct MoÀMo bond photolysis was used throughout the study,m icroviscosity should also be important for aradicalpair generated from an azo initiator.…”
mentioning
confidence: 99%
“…The molecular structure of a liquid or of a polymer should be taken into account under consideration of diffusion of reagents at a distance of few ρ 12 [6]. A promising approach is using quantitative values of "microviscosity" affecting ϕ [34]. It is important to learn where guest molecules are located in a polymer.…”
Section: Discussionmentioning
confidence: 99%